1990
DOI: 10.1111/j.1439-0442.1990.tb00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Boar Semen in Mini‐ and Maxi‐Straws

Abstract: Split ejaculates from four boars were frozen with a programmable freezing machine, in mini-(0.25 ml) and maxi-(5 ml) plastic straws with an extender at either acidic (6.3) or alkaline (7.4) pH. Glycerol (3%) was used as cryoprotectant. The freezing of the semen was monitored by way of thermocouples placed in the straws. Post-thaw motility and acrosome integrity were evaluated; the latter using phase contrast microscopy, eosin-nigrosin stain and electron microscopy. Post-thaw sperm motility was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 15 publications
1
42
1
4
Order By: Relevance
“…In our study, the sperm motility percentages obtained are lower than the standard values for post-thawed semen in non-Iberian boars (45-50%; Bwanga et al 1990). However, no real data exist for this parameter in Iberian boars and differences in experimental design, package systems, breeds or individual male responses to Immunological study of cryopreserved sperm cryopreservation must also obviously be taken into account.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In our study, the sperm motility percentages obtained are lower than the standard values for post-thawed semen in non-Iberian boars (45-50%; Bwanga et al 1990). However, no real data exist for this parameter in Iberian boars and differences in experimental design, package systems, breeds or individual male responses to Immunological study of cryopreserved sperm cryopreservation must also obviously be taken into account.…”
Section: Discussioncontrasting
confidence: 61%
“…Several other authors have also observed an increase of 50-60% altered acrosomes after thawing (Bwanga et al 1990, Fiser & Fairfull 1990, Hofmo & Almlid 1991, Verheyen et al 1993.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Boar epididymal spermatozoa can be frozen and used for IVF [2]. Normally, before freezing, they are diluted with extenders at a temperature of between 15 C and 4 C, then gradually cooled to 4 C and cryopreserved, using the same procedure as for ejaculated boar spermatozoa (reviewed by Bwanga [14]). …”
Section: Discussionmentioning
confidence: 99%